FOLK MUSIC OF WESTERN ODISHA ‘GANDA BAJA’ THE TRADITION IN TRANSITION - Prajapati, Deep (ShodhKosh: Journal of Visual and Performing Arts, 2022)
'Ganda Baja’ is a hardly discussed topic in scholastic works of Indian folk music. It is one of the major and unique folk music traditions in western-Odisha folk culture. Presently, it is going through a phase of transition which could determine its very existence. The new generation constantly in a search to contextualize the music that would sound trendy to the present-day music market, yet it is searching scopes to reach a level in terms of music quality and to justify the core. On the other hand, the cultural elites trying to filter the music that would be conducive to proscenium, but the original music and musicians remain marginalized. With the notion of up grading music, somewhere the transition is causing a distortion to the music and rarely addressed with that gravity. However, the traditional musicians and their music have always been rooted in traditional aesthetics. This study addresses on few degenerative factors that causing a huge distortion to Ganda Baja in the process of transition. The distortions that need more scholastic attentions are (1) the changing styles of music performance practices and the platforms, (2) the music making with overridden musical assimilation, and (3) the changing connotations in the scholastic works. The Ganda Baja musicians are excluded in current cultural happenings. This study aims at bringing Ganda Baja and the musicians to limelight both in the music literature and cultural platforms. It invites scholastic attentions to way out solutions that would produce music without a distortion.